HCV and HCC molecular epidemiology - Pujol, Flor H. (Iatreia, 2007)
iHepatitis C virus (HCV) is a member of the family Flaviviridae, responsible for the majority of the non-A non-B post-transfusion hepatitis before 1990. Around 170 millions persons in the world are thought to be infected with this virus. A high number of HCV-infected people develop cirrhosis and from these, a significant proportion progresses to hepatocellular carcinoma (HCC). Six HCV genotypes and a large number of subtypes in each genotype have been described. Infections with HCV genotype 1 are associated with the lowest therapeutic success. HCV genotypes 1, 2, and 3 have a worldwide distribution. HCV subtypes 1a and 1b are the most common genotypes in the United States and are also are predominant in Europe, while in Japan, subtype 1b is predominant. Although HCV subtypes 2a and 2b are relatively common in America, Europe, and Japan, subtype 2c is found commonly in northern Italy. HCV genotype 3a is frequent in intravenous drug abusers in Europe and the United States. HCV genotype 4 appears to be prevalent in Africa and the Middle East, and genotypes 5 and 6 seem to be confined to South Africa and Asia, respectively. HCC accounts for approximately 6% of all human cancers. Around 500,000 to 1 million cases occur annually worldwide, with HCC being the fifth common malignancy in men and the ninth in women. HCC is frequently a consequence of infection by HBV and HCV. The first line of evidences comes from epidemiologic studies. While HBV is the most frequent cause of HCC in many countries of Asia and South America, both HBV and HCV are found at similar frequencies, and eventually HCV at a higher frequency than HBV, among HCC patients in Europe, North America, and Japan. The cumulative appearance rate of HCC might be higher for HCV-infected cirrhotic patients than for HBVinfected ones. HCV genotype 1b has also been more frequently associated with a more severe liver disease. However, this association seems to be due to the fact that individuals infected with this genotype have a longer mean duration of infection. An heterogeneity in the IFN sensitivity determining region (ISDR) of HCV genotype 1b isolates has been observed in patients presenting with HCC, compared with the isolates of patients presenting with liver cirrhosis without HCC, which exhibit a more homogeneous ISDR region, although an opposite observation has been reported by others. Some nucleotides in the 5’ non-coding region and specific amino acid substitutions within the entire HCV genome have been also found in the HCV strains infecting patients with HCC. Hepatic steatosis is a common consequence of HCV infection, particularly HCV genotype 3, and has been recently associated with the development of HCC. Steatosis might be contributing to the progression of fibrosis in HCV-related disease. More studies are needed to evaluate an eventual correlation between HCV genotype 3, the presence of steatosis, and progression to HCC. Even if it seems that an effective vaccine against HCV will not be readily obtained in the near future, available therapeutic approaches seem to delay the progression to HCC in infected patients who respond at least transiently to treatment. The evolution to HCC associated with infection by HCV seems to be a multifactor process. Although the role of chronic infection with HCV in the etiology of liver cancer is well established, more studies are needed to assess the individual contribution of specific viral strains in the development of HCC. The limited arsenal available against HCV (improving therapeutic agents) is crucial since it might prevent or delay the development of HCC. REFERENCES 1. Pujol, F.H. & Devesa, M. (2005). Genotypic Variability of Hepatitis Viruses Associated to Chronic Infection and to the Development of Hepatocellular Carcinoma. J. Clin. Gastroenterol. 39: 611-618.